Response of Fumaric Acid Addition on Methanogenesis, Rumen Fermentation, and Dry Matter Degradability in Diets Containing Wheat Straw and Sorghum or Berseem as Roughage Source. (17th April 2012) - Sirohi, S. K.; Pandey, Poonam; Goel, Navneet
Abstract : An in vitro incubation system was used to evaluate effect of supplementation of fumaric acid at 0, 5, 10, and 15 mM concentration in high-, medium-, and low-fiber wheat straw containing total mixed diets with sorghum ( Sorghum vulgare ) and berseem clover ( Trifolium alexandrinum L. ) on rumen fermentation, methane production, and gas kinetics parameters. Three types of diets were prepared with different roughage and concentrate ratio (80 : 20, 50 : 50, and 20 : 80) by taking the representative samples. The roughage part composed of wheat straw (70 parts) and sorghum (30 parts) or berseem (30 parts) and the concentrate part composed of maize (33%), GNC (21%), mustard cake (12%), wheat bran (20%), deoiled rice bran (11%), mineral mixture (2%), and salt (1%). Fumaric acid was added in incubation medium to achieve final concentration of 0, 5, 10, and 15 mM. All the treatment combinations were arranged in 4 × 3 factorial designs with three replicates. It was concluded from the study that fumaric acid addition (5–15 mM) in diets varying in roughage to concentrate ratio significantly (P ≤ 0.05 ) reduced the methane production without affecting dry matter digestibility and maximum reduction was noticed at 5 mM concentration.